The Development of Malang Raya Tourism Bilingual Catalog - Dian Adi Pratiwi; Tiksno Widyatmoko (Universitas Negeri Malang, 2020)
This study aimed to develop a tourism catalog of Malang Raya that compiled in bilingual, Indonesian and German. The product has been through a validation process by the media expert and material expert. The field trial was conducted by 10 respondents of the Indonesian Literature Department State University of Malang. The instrument used in this study was a questionnaire sheets. This study employed was descriptive quantitative research. The result of this study stated that the catalog is suitable to be used as a tourism reference in Malang Raya, and as literature readings for the related institutions in terms of Malang Raya tourism.